Type 2 Diabetes as a Predictor of Muscle Strength Decline over 11 years among Men and Women Aged 55 Years and Older - Tiainen Kristina; Raitanen Jani; Strandberg Timo; Koskinen Seppo; Stenholm Sari (KARGER, 2022)
Background: Long-term associations between type 2 diabetes, prediabetes, and muscle strength are obscure in older adults. The aim of this study was to examine type 2 diabetes as a predictor of handgrip strength decline during an 11-year follow-up among men and women aged 55 years.
Methods: We used Finnish population-based Health 2000 Survey and its follow-up measurements in 2011. The study population consisted of 1,200 individuals, aged 55-86 years at baseline. Baseline fasting glucose level or use of diabetes medication was used to categorize the participants into diabetes (≥7.0 mmol/L), prediabetes (≥6.1 mmol/L but <7.0 mmol/L), and nondiabetes (<6.1 mmol/L) groups. Handgrip strength was measured at baseline and during 11-year follow-up.
Results: Mean handgrip strength at baseline did not differ between diabetes groups in men or women. Among men during the 11-year follow-up, decline in muscle strength was significantly greater among diabetes group (-131.5 Newtons [N], 95% confidence interval (CI) -182.7 to -80.4) than nondiabetes group (-98.9 N, 95% CI -139.5 to -58.3) after adjusting for age, education, lifestyle factors, chronic conditions, and diabetes status at follow-up. Among women, muscle strength decline did not differ between diabetes, prediabetes, or nondiabetes groups after adjusting for all potential covariates, the results being -45.0 N (95% CI -73.2 to -16.7), -29.4 N (95% CI -59.7 to 0.9), and -42.3 N (95% CI -70.5 to -14.1), respectively.
Conclusions: The presence of type 2 diabetes was associated with greater muscle strength decline among older men but not among older women.